Beyond Netizen: Understanding Communication Norms in Islamic Perspective - Riza Adrian Soedardi (UIN Raden Mas Said Surakarta, 2019)
Instagram is one of the popular social media among Indonesia because it provides facilities for communicating and expressing the users. Yet, the popularity of Instagram emerges problems such as cyberbullying and harassment. Therefore, this study attempts to examine communication norms among netizen in their comments on Instagram based on the Islamic perspective. The method used in this research is communication approach and linguistic perspective to elaborate the social media phenomena and to examine the language used on the comments. This result shows that communication schema on Instagram represents users so that Muslim in Indonesia should keep away from cyberbullying and harassment in social media, especially on Instagram.